The Effects of Pilates and Conventional Treatment Methods in The Management of Stress Urinary Incontinence Among Women : Life Sciences- Physiotherapy - Kirthika.S, Veena; M, Swetha.; Sudhakar, Selvaraj; Arunselvi, J.; V, Saravanan.; Rajalakshmi, G.; T, Bharaneedharan. (International Journal of Life Science and Pharma Research, 2023)
Stress Urinary Incontinence is a common condition among women that requires attention. The main aim of thisstudy was to compare the effects of Pilates and conventional treatment methods in managing stress urinary incontinence amongwomen. This study is an experimental design, comparative pre-post-test type. 30 female subjects with stress urinaryincontinence were randomly divided into groups, Group A and Group B, with 15 subjects in each group. Group A receivedPilates exercises, and Group B subjects received conventional Kegel’s exercises. The study duration was 12 weeks. The pad test,cough stress test, and International Consultation on Incontinence (ICIQ) Questionnaire were outcome measures. The results ofthis study revealed that on comparing the Mean values of Group A & Group B on the International Consultation onIncontinence Questionnaire (ICIQ) and Pad test, Group A (Pilates Exercise) showed 4.46 and 4.93 post-test values which weremore effective than Group B (Conventional kegel’s Exercise) at 8.60 and 9.46 at P ≤ 0.001. The Pilates group experienced ahighly significant improvement on the cough stress test compared to the conventional group at P< 0. 001.Pilates exercises wereproven highly effective in managing stress urinary incontinence among women. This study is one of its kind, which demonstratedthe effect of Pilates and its clinical usage for the effective management of Stress Urinary Incontinence.